Curriculum development for learning to live together: The Caribbean sub-region: The final report of the sub-regional seminar held in Havana, Cuba, 15-18 May 2001 - (:unkn) unknown (International Bureau of Education, 2001)
The seminar brought together 26 participants from 20 member states of UNESCO/CARNEID. The principal issues addressed during the seminar related to three themes: 1) Citizenship education: Learning at school and in society; 2) Social exclusion and violence: Education for social cohesion; and 3) Shared values, cultural diversity and education: What to learn and how? The seminar consisted of a number of lecture presentations by Caribbean and non-Caribbean experts, followed by plenary discussions and workshops that explored aspects of the themes and looked at practical ways of implementing them in the school curriculum. In Part 1, the report provides a synthesis of the national presentations on curriculum development processes and reforms by a number of countries participating at the seminar. Parts II, III and IV include the various lecture presentations made and the outcomes of the three workshops. Part V summarizes the final debate.
Keywords: Citizenship education